The influence of environmental temperature and humidity on temporal decomposition of cockroach allergens Bla g 1 and Bla g 2 in feces - Erban, Tomas; Stejskal, Vaclav; Aulicky, Radek; Krizkova-Kudlikova, Iva; Nesvorna, Marta; Hubert, Jan (Journal of medical entomology, 2010)
The aim of the study was to establish a model of the environmental fate of German cockroach (Blattella germanica L.) allergens Bla g 1 and Bla g 2 in feces under controlled and field conditions. Temporal decline (3, 6, and 9 mo) of allergens Bla g 1 and Bla g 2 in the feces protected from cleaning was measured under laboratory and experimental household conditions. The influence of environmental temperature (15, 20, 25, 30, and 35 degrees C) and moisture (53, 75, 85, and 100% RH) on allergen degradation was estimated for 3, 6, and 9 mo. Bla g 1 was more stable than Bla g 2 and the proteins. The proteins and Bla g 2 contents were correlated negatively with the decomposition time; Bla g 1 was not. However, when the content of Bla g 1 in control and exposed tubes was compared, the decrease after exposure was significant at exposure in 35 degrees C, 53 and 100% RH. In laboratory, the shortest half-life (16-38 d) of Bla g 2 was at high temperature and humidity (100% RH at 35 degrees C), whereas the longest half-life (340 d) was at 25 degrees C and 85% RH. In the apartment, the half-life was 406 d. The results indicate that Bla g 1 and Bla g 2 allergens can persist in feces for several months under usual household humidity and temperature.
Keywords: Cockroaches; Feces; teplota; vlhkost; Animals; feces; švábi; alergeny; aspartátové endopeptidasy; Allergens; zvířata; Aspartic Acid Endopeptidases; Temperature; antigeny rostlinné; Antigens, Plant; Humidity